2018
DOI: 10.1016/j.bbmt.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Relapse Incidence with FLAMSA–RIC Compared with Busulfan/Fludarabine for Acute Myelogenous Leukemia Patients in First or Second Complete Remission: A Study from the Acute Leukemia Working Party of the European Society for Blood and Marrow Transplantation

Abstract: Busulfan/fludarabine (BuFlu) is a widely used conditioning regimen for patients with myeloid malignancies. The sequential FLAMSA (fludarabine + Ara-C + amsacrine chemotherapy) protocol followed by either cyclophosphamide and total body irradiation (FLAMSA-TBI) or cyclophosphamide and busulfan (FLAMSA-Bu) has shown remarkable activity in high-risk acute myelogenous leukemia (AML) patients. Here we compare the outcomes of AML patients transplanted in first complete remission (CR1) or second complete remission (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
1
13
0
1
Order By: Relevance
“…Interestingly, new combinations including these drugs are still being tested in clinical trials. For example, a recent trial found that mAMSA could reduce relapse incidence in AML-patients [ 66 ].…”
Section: Top2b As An Anti-cancer Drug Targetmentioning
confidence: 99%
“…Interestingly, new combinations including these drugs are still being tested in clinical trials. For example, a recent trial found that mAMSA could reduce relapse incidence in AML-patients [ 66 ].…”
Section: Top2b As An Anti-cancer Drug Targetmentioning
confidence: 99%
“…A total of eighteen articles underwent full-text review and 9 of them were excluded because they did not report the primary outcomes of interest. Finally, 12 studies fulfilled the eligibility criteria and were included in the meta-analysis [3,6,7,8,9,10,11,12,13,14,15,16]. A manual review of the bibliography of the included studies, and some selected review articles, did not yield any additional eligible studies.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of fludarabine, amsacrine, and cytarabine (FLAMSA)-polychemotherapy with RIC was initially adopted by Schmid et al for patients with high-risk myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML) [3,4,5] to combine high anti-leukemic activity with the advantages of RIC. Although several variations have been published [6,7,8,9,10,11,12,13,14,15,16], the ‘classic’ FLAMSA-RIC regimen consists of fludarabine, amsacrine, and cytarabine, followed by RIC with 4-Gy total body irradiation (TBI), high-dose cyclophosphamide (Cy), antithymocyte globulin (ATG), and prophylactic donor lymphocyte infusions (DLI) if indicated. Because of initially promising data, especially in poor prognosis AML patients, FLAMSA-RIC was adopted by many transplantation centers, and variations that included busulfan (Bu) or treosulfan were established.…”
Section: Introductionmentioning
confidence: 99%
“…De novo non-M3 AML patients have a high overall mortality rate, ranging from 60% to 76% at 5-year. [7][8][9][10] Accurate prognostic models for individuals are needed, not only to select appropriate treatment regimens but also to inform patients regarding their long-term outcomes (which may aid them in their goals of care decisions). Mohamed et al developed an AML composite model, to estimate the risk of death within 1 year after initial chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Furthermore, 5-year overall survival (OS) for patients with non-M3 AML range from 24% to 40%. [7][8][9][10] Currently, several factors which can aid with prognostication and prediction of clinical outcomes [e.g., risk strati cation, age, white blood cell (WBC) count, coexisting comorbidities and a history of an antecedent hematologic disorder]. [2,3,[11][12][13][14][15][16][17] The European Leukemia Net(ELN) [3] and National Comprehensive Cancer Network(NCCN) [2] risk strati cations are the most widely used criteria to stratify patients with AML.…”
Section: Introductionmentioning
confidence: 99%